Effectiveness of bioinsecticides for different applications against the main pests of radish - Shchetina, S.; Mostoviak, I.; Fedorenko , V. (Quarantine and plant protection, 2024)
Goal. To determine the technical effectiveness of bioinsecticides against major insect pests of radish (Raphanus sativus (L.) convar. radicula (Pers) Sazon.) grown in open fields, and their impact on plants, yield, and root crop quality. Methods. The study was conducted in accordance with the methods generally accepted in entomology and vegetable growing. During 2020—2022 in open ground conditions on three radish hybrids of different ripeness groups (Adele, Eliza and Stellar) the effectiveness of bioinsecticides Bitoxibacillin-BTU, p. (cell bacteria Bacillus thuringiensis-endospores, titer 1.0 × 10⁹ CFU/ cm3, CS +), 2 l/ha, ACTOVERM FORMULA, CE (abamectin, 18 g/l), 5 l/ha, Lepidocide-BTU, p. (cells of the bacterium Bacillus thuringiensis-var. Kurstaki 9708 L, endospores less than 1 × 109 CFU/cm3), 4 l/ ha, (control). The preparations were applied by spraying plants and fertigation (introduction of fertilizers or pesticides into the irrigation system). Results. On the 14th day after spraying radish plants with Bitoxybacillin-BTU, the population of crucifer flea beetles decreased by 3.9—5.2 times and by 2.8—3.9 times with fertigation. The population of cabbage aphids decreased by 3.9—4.8 and 3.0—3.5 times, and cabbage moth by 5.0—9.0 and 2.7—5.0 times, respectively. The technical effectiveness of Bitoxybacillin-BTU was 76% and 68% against crucifer flea beetles, 78% and 70% against cabbage aphids, and 83% and 73% against cabbage moth. The application of ACTOVERM FORMULA by spraying reduced the population of crucifer flea beetles by 2.6—3.3 times and by 2.5—2.7 times with fertigation. The population of cabbage aphids decreased by 2.9—3.6 and 2.5—2.8 times, and cabbage moth by 2.0—3.0 and 2.0—5.0 times, depending on the radish hybrid. The technical effectiveness of ACTOVERM FORMULA against these pests was 67%, 70%, and 77% with spraying, and 60%, 62%, and 73% with fertigation, respectively. No negative effects from spraying or fertigation with bioinsecticides on radish plants were detected. However, radish plants in the spray treatment had higher height (by 2—3 cm), more leaves per plant (by 1 leaf), and a larger leaf surface area (by 0.2—0.8 thousand m²/ha), depending on the hybrid and product. The root mass increased in treatments with double spraying of ACTOVERM FORMULA and Bitoxybacillin-BTU compared to control and fertigation. The use of bioinsecticides Bitoxybacillin- BTU and ACTOVERM FORMULA (2 treatments) during vegetation ensured yields of 25.6—25.8 t/ha for the Adele hybrid with 93—94% marketable root crops, 24.0—25.1 t/ha for the Eliza hybrid with 94—95% marketable root crops, and 23.2—23.7 t/ha for the Stellar hybrid with 95—96% marketable root crops. The root crops had high dry matter content (Adele: 7.9—8.2%, Eliza: 6.2—6.3%, Stellar: 6.5—6.7%), total sugars (Adele: 2.4—2.5%, Eliza: 2.1—2.2%, Stellar: 2.6%), and ascorbic acid content (Adele: 26.0—26.2 mg/100 g, Eliza: 23.9—24.0 mg/100 g, Stellar: 25.4—25.5 mg/100 g). Conclusions. The application of bioinsecticides Bitoxybacillin-BTU (2 l/ha) and ACTOVERM FORMULA (5 l/ ha) is an effective method for controlling sucking pests in radish crops. Double spraying of radish plants at BBCH 0—9 and BBCH 12—19 with Bitoxybacillin-BTU (2 l/ha) provided control of crucifer flea beetle (76%), cabbage aphid (78%), and cabbage moth (83%). Double spraying with ACTOVERM FORMULA (5 l/ha) at the same stages provided control of crucifer flea beetle (67%), cabbage aphid (70%), and cabbage moth (77%).